Self-metathesis of methyl oleate on silica-supported Hoveyda-Grubbs catalysts - Zelin, Juan (2013)
The self-metathesis of methyl oleate (MO) to yield 9-octadecene and 9-octadecene-1,18-dioate (9-OD) was studied in liquid-phase on silica-supported Hoveyda–Grubbs complex catalysts (HG/SiO2) containing 0.43–6.0 wt.% HG. The reaction was carried out in a batch reactor at 303–343 K and 101.3 kPa, using cyclohexane as solvent. HG/SiO2 catalysts were active and highly selective for the MO metathesis reaction; equilibrium values of MO conversion and 9-OD yield were reached in 80 min. No catalyst leaching took place in cyclohexane. Catalysts containing HG N0.87 wt.% showed no significant deactivation after two consecutive catalytic tests.